Changes in the strategic internal control of companies under crisis pressure - Lyudmila Mihaylova; Emil Papazov (Trends Economics and Management, 2021)
Purpose of the article: The article aims at presenting and analysing key changes in the strategic internal control of companies under the pressure of crisis phenomena. The research question is how to adapt the strategic internal control to an evolving crisis through inclusion of control environmental sustainability measures, and strategic model adaptation. Methodology: A qualitative approach has been applied along with the research of larger companies from the brewery sector and small-and medium sized enterprises from the knitted fabrics manufacturing sector in Bulgaria. The study has also taken into consideration some companies' strategic documents, as well as interviews with companies' managers. The gathered information has been systematized, compared and evaluated with the help of the "Relative (Competitive) Advantage Matrix" model. Scientific aim: Understanding the impact of changes in strategic internal control on management under the pressure of crisis phenomena. Findings: The analysing of the quasi-control environment and competitive advantages is an important strategic management issue during crises. Competitive advantages derive mainly from the characteristics of the product (or service) that make it better than the products (or services) of competitors and they are associated with changes in the strategic internal control of companies under the pressure of hard times. Conclusions: Strategic internal control has to be adapted to the crisis situation through control environmental sustainability measures, strategic model adaptation and selected competitive advantages. Business processes are changing as a result of crisis times, then the control environment, risk assessments and competitive advantages need to be more detailed and analysed in different aspects. At the same time, the strategic internal control in hard times faces unexpected results, such as a drastic reduction in the incomes, a decrease in retail sales or a drastic increase in online sales. Using the collected information, comparisons can be made to better outline similarities and differences that will point out ways for improvement. This information should be brought to the attention of the personnel of the companies. The change in the activities should not be delayed in time, since information quickly becomes out-dated.
Keywords: M21; L1; 650; strategic control; management; crisis phenomena; internal control